An Analysis and Strategies to Enhance Students Interest and Participation in Informatics Learning on App Inventor Topic Utilizing Mobile Devices: A Case Study of Classroom Learning Sessions in Class of F6 at SMA Negeri 4 Surakarta - Davina, Indri Heldy; Maryono, Dwi; Waskito, Adi (Politeknik NEST, 2024)
This research aims to analyze and develop strategies that can enhance students' interest and participation in informatics learning on App Inventor subject using mobile devices, with a case study of classroom learning sessions in class of F6 at SMA Negeri 4 Surakarta. The research method used is a qualitative method. Data collection methods in this research include observation, distributing questionnaires to students, and teacher interview. Respondents in this study were a class of F6 students totaling 31 people, consisting of 10 female students and 21 male students. The limitation in this study is that only a small number of students bring laptops to informatics lesson. The results showed that the school's slow internet connection, lack of interest in bringing laptops, lack of skills in using laptops, and the availability of personal laptops were the main challenges to student participation in teaching and learning activities, especially in App Inventor subject. However, using certain strategies such as optimizing the use of mobile devices enables continuous learning inside and outside the classroom.